Perception of Organizational Politics, Job Satisfaction and Bio-Social Variables (Malaysian Management Journal, 1997)
This study was conducted to examine the nature of the perception of organizational politics and its relationÂship with job satisfaction and bio-social variables. Using a questionnaire, data was collected on 142 superÂvisory personnel- The results indicate that the perception. of organizational politics consists of seven factor dusters. These are, impression management, clique behaviour, selection system, performance expectation, reward system, supervisory communication and ca-worker behaviour. The results -reconfirm the general finding of a negative relationship between job satisfaction and perception of organizational politics. Of the seven factors, impression management and supervisory communication contribute significantly to job satisfaction. While none of the bio-social variables showed any significant relationship with perception of organizational politics, on the whole, race, years of formal education and total years of experience showed significant differences/ relationships with the factors of performance expectation, co-worker behaviour and supervisory communication. These results are explained with reference to the Malaysian, context.